Software mistakes and tradeoffs - Lelek, Tomasz; Skeet, Jonathan (Manning Publications, 2022)
Optimize the decisions that define your code by exploring the common mistakes and intentional tradeoffs made by expert developers. In Software Mistakes and Tradeoffs you will learn how to: Reason about your systems to make intuitive and better design decisions Understand consequences and how to balance tradeoffs Pick the right library for your problem Thoroughly analyze all of your service's dependencies Understand delivery semantics and how they influence distributed architecture Design and execute performance tests to detect code hot paths and validate a system's SLA Detect and optimize hot paths in your code to focus optimization efforts on root causes Decide on a suitable data model for date/time handling to avoid common (but subtle) mistakes Reason about compatibility and versioning to prevent unexpected problems for API clients Understand tight/loose coupling and how it influences coordination of work between teams Clarify requirements until they are precise, easily implemented, and easily tested Optimize your APIs for friendly user experience Code performance versus simplicity. Delivery speed versus duplication. Flexibility versus maintainability--every decision you make in software engineering involves balancing tradeoffs. In Software Mistakes and Tradeoffs you'll learn from costly mistakes that Tomasz Lelek and Jon Skeet have encountered over their impressive careers. You'll explore real-world scenarios where poor understanding of tradeoffs lead to major problems down the road, so you can pre-empt your own mistakes with a more thoughtful approach to decision making. Learn how code duplication impacts the coupling and evolution speed of your systems, and how simple-sounding requirements can have hidden nuances with respect to date and time information. Discover how to efficiently narrow your optimization scope according to 80/20 Pareto principles, and ensure consistency in your distributed systems. You'll soon have built up the kind of knowledge base that only comes from years of experience. About the Technology Every step in a software project involves making tradeoffs. When you're balancing speed, security, cost, delivery time, features, and more, reasonable design choices may prove problematic in production. The expert insights and relatable war stories in this book will help you make good choices as you design and build applications. About the Book Software Mistakes and Tradeoffs explores real-world scenarios where the wrong tradeoff decisions were made and illuminates what could have been done differently. In it, authors Tomasz Lelek and Jon Skeet share wisdom based on decades of software engineering experience, including some delightfully instructive mistakes. You'll appreciate the specific tips and practical techniques that accompany each example, along with evergreen patterns that will change the way you approach your next projects. What's Inside How to reason about your software systematically How to pick tools, libraries, and frameworks How tight and loose coupling affect team coordination Requirements that are precise, easy to implement, and easy to test About the Reader For mid- and senior-level developers and architects who make decisions about software design and implementation. About the Authors Tomasz Lelek works daily with a wide range of production services, architectures, and JVM languages. A Google engineer and author of C# in Depth, Jon Skeet is famous for his many practical contributions to Stack Overflow. Quotes Great book that I wish I had earlier in my career. Many hard-learned lessons contained in these pages. - Dave Corun, Avanade Clear and to-the-point summation of years of real-life experience in software engineering. A must-read for all newcomers to the software engineering world. - Rafael Avila Martinez, Mastercard Shines a light on the intrinsic conflicts of the programming process and how they impact the code you write. - Roberto Casadei, Università di Bologna Summarizes the main pain points for every software developer and presents solutions in a clear and didactic way. - Nelson González, General Electric.